Greenbug resistance in barley landraces from Uzbekistan - E. E. Radchenko; K. D. Dyatlova; D. E. Akimova; I. A. Zveinek (Труды по прикладной ботанике, генетике и селекции)
Background. The greenbug (Sсhizaphis graminum Rondani) can significantly reduce the yield of barley and other cereals in the southern regions of Russia. Cultivation of resistant varieties can significantly limit the pathogen’s harmfulness. At the same time, specific interaction with the genotypes of the host plant, characteristic of S. graminum, requires a continuous search for new resistance donors to broaden the genetic diversity of barley cultivars. Materials and methods. The resistance of 178 accessions of barley landraces from Uzbekistan to the Krasnodar greenbug population was tested in laboratory experiments. Juvenile plants were infested with aphids of different ages, and when the susceptible control died (cv. ‘Belogorsky’), resistance was assessed on a 0 to 10 (plant death) rating scale. Plants with a damage rate of 1–4 points (up to 30% of the leaf surface being damaged) belonged to the resistant class; damage rate of 5–8 points indicated moderate resistance of plants, and that of 9–10 meant susceptibility. In addition, we assessed the aphid damage of the winter barley cultivar ‘Post’, protected by the previously identified resistance gene Rsg1.Results and conclusions. We identified 52 barley accessions as heterogeneous for the studied trait. In six accessions, plants with high (points 3 to 4) and moderate (5 to 8) resistance were identified; 6 accessions were differentiated into 3 phenotypic classes: resistant, moderately resistant, and susceptible; and in 40 accessions the manifestation of the resistance component varied within 5 to 7 points (from 31 to 60% of the leaf surface being damaged). The distinctly expressed resistance of 12 accessions is controlled by alleles of resistance genes that differ from Rsg1. After selection for resistance, the identified accessions can be used in breeding.